Synthetic method for catalytic oxidation of glyoxal by using composite catalyst

By loading zeolite and nano-lanthanum oxide on the copper mesh surface and depositing nanosilver in the electrolyte, the problem of silver catalyst agglomeration at high temperature is solved, the yield of glyoxal is improved, and the good dispersion and stability of the catalyst is achieved. .

CN119118803APending Publication Date: 2024-12-13FUYANG FENG CHI CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411242284.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, silver catalysts are prone to agglomeration under high temperature conditions, resulting in a lower yield of glyoxal.

Method used

Using composite catalyst, nanosilver is deposited in electrolyte by loading zeolite and nanolanthanum oxide on the surface of the copper mesh, and depositing nanosilver in the electrolyte. The combined action of copper mesh, zeolite and nanolanthanum oxide is used to prevent nanosilver agglomeration and improve the dispersion and stability of the catalyst. sex.

Benefits of technology

It effectively improves the yield of glyoxal, ensures that the catalyst is not prone to agglomeration at high temperatures, and promotes the reaction of converting ethylene glycol into glyoxal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005029643090000071
    Figure BDA0005029643090000071
  • Figure BDA0005029643090000081
    Figure BDA0005029643090000081
Patent Text Reader

Abstract

The invention relates to the technical field of chemical raw material preparation, and particularly discloses a synthesis method for catalytic oxidation of glyoxal with a composite catalyst. Under the combined action of the copper net, the zeolite and the nano lanthanum oxide, the nano silver in the composite catalyst can keep a good dispersion state and is not easy to agglomerate in a high-temperature state, so that the reaction of converting ethylene glycol into glyoxal can be fully promoted, and the yield of glyoxal can be increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical raw material preparation, and more specifically, to a method for synthesizing glyoxal by catalytic oxidation of a composite catalyst. Background Art

[0002] Glyoxal is a widely used fine chemical product with a molecular formula of C 2 H 2 O 2 , can be used in many fields such as drug manufacturing, fragrance synthesis, paints and coatings, adhesives, etc. Japan, the United States, and Western Europe have done a lot of research in this regard. At present, my country's glyoxal is mainly used in the textile industry and the manufacture of pharmaceutical intermediates, and there is an optimistic prospect for further development and utilization of glyoxal and its series of products.

[0003] At present, the synthetic method of glyoxal is mainly ethylene glycol gas phase catalytic oxidation method, and the principle of ethylene glycol gas phase catalytic oxidation method is to mix ethylene glycol after heating vaporization with inert gas (such as water vapor), air and circulating gas, and form glyoxal gas under catalyst action. After glyoxal gas is absorbed by water for many times, glyoxal product can be obtained through decolorization. In the above method, catalyst is usually selected from silver catalyst.

[0004] With respect to the above-mentioned related technologies, the inventors believe that although the methods in the related technologies can achieve the preparation of glyoxal, the particles of the silver catalyst are prone to agglomeration under high temperature conditions, and the agglomeration of the silver catalyst will have an adverse effect on the reaction, so it is difficult to obtain a higher glyoxal yield. Summary of the invention

[0005] In the related art, the particles of the silver catalyst are prone to agglomeration under high temperature conditions, making it difficult to obtain a high yield of glyoxal. In order to improve this defect, the present application provides a method for synthesizing glyoxal by catalytic oxidation of a composite catalyst.

[0006] The present application provides a method for synthesizing glyoxal by catalytic oxidation of a composite catalyst, which adopts the following technical scheme: A method for synthesizing glyoxal by catalytic oxidation of a composite catalyst comprises the following steps: (1) preheating and vaporizing ethylene glycol to obtain ethylene glycol vapor, mixing the ethylene glycol vapor, protective gas, air and circulating gas to obtain raw gas, and then preheating the raw gas for standby use; (2) inputting the raw gas into a catalytic reactor equipped with a composite catalyst, reacting under heating and pressurizing conditions, cooling the product with water after the reaction is completed, and then transporting it to an absorption tower for repeated absorption to obtain a crude glyoxal solution, and distilling, purifying and decolorizing the crude glyoxal solution to obtain glyoxal; the composite catalyst is a copper mesh catalyst with zeolite, nano-silver and nano-lanthanum oxide loaded on the surface; (3) The tail gas is treated in the absorption tower and the scrubbing tower, and after the waste gas that meets the emission standards is discharged, the remaining tail gas is used as the circulating gas.

[0007] By adopting the above-mentioned technical scheme, the application is loaded with zeolite, nano silver and nano lanthanum oxide to the copper mesh surface, obtained composite catalyst, and used this composite catalyst to replace traditional silver catalyst, obtained new glyoxal synthesis method. In the method of the present application, copper mesh and zeolite are used as the carrier of nano silver together, can play the effect of dispersion, stable nano silver particles, and the adding of nano lanthanum oxide can play the physical isolation effect, on the one hand, make nano silver just have less particle diameter when generating, on the other hand, also hinder the reunion of nano silver under hot conditions. Under the joint action of copper mesh, zeolite and nano lanthanum oxide, the nano silver in the composite catalyst can keep a good dispersed state, and is not easy to reunite under hot conditions, thereby can fully promote the reaction of ethylene glycol conversion into glyoxal, help to improve the productive rate of glyoxal.

[0008] Preferably, the composite catalyst is prepared according to the following method: (1) loading nano zeolite on the surface of a copper mesh to obtain a copper mesh substrate for later use; (2) mixing an inorganic base, a silicon source, an aluminum source, nano-lanthanum oxide and water to obtain a growth solution for later use; (3) immersing the copper mesh substrate into a zeolite growth solution for ultrasonic hydrothermal treatment to obtain a zeolite-modified copper mesh; (4) The zeolite-modified copper mesh is immersed in a silver nitrate electrolyte as a cathode, and silver is used as an anode for electrolysis, and ultrasonic treatment is performed. After the electrolysis is completed, the electrolysis product is calcined in air to obtain a composite catalyst.

[0009] By adopting the above technical scheme, the present application hydrothermally treats the copper mesh substrate in the growth liquid, uses nano zeolite as a seed to induce the growth of zeolite, and obtains a copper mesh with a zeolite film on the surface, that is, a zeolite-modified copper mesh. While the zeolite film is formed, nano lanthanum oxide will combine with the zeolite film, so the zeolite film surface of the zeolite-modified copper mesh will contain a certain amount of nano lanthanum oxide. In step (3), nano silver is deposited on the surface of the zeolite film, and the nano lanthanum oxide reduces the particle size of nano silver through physical isolation. The zeolite film and the copper mesh serve as carriers together, thereby obtaining a composite catalyst in which nano silver is evenly dispersed and not easy to agglomerate.

[0010] Preferably, in step (1) of preparing the composite catalyst, the nano zeolite is loaded on the surface of the copper mesh according to the following method: (1) impregnating the copper mesh with a cationic polyelectrolyte solution and an anionic polyelectrolyte solution in sequence, then taking out the copper mesh and washing it to obtain a pretreated copper mesh; (2) impregnating the pretreated copper mesh with a cationic polyelectrolyte solution and a nano-zeolite dispersion solution in sequence, and then taking out the pretreated copper mesh and washing it; (3) Repeat step (2) multiple times to obtain a copper mesh substrate.

[0011] By adopting the above technical scheme, the present application pre-treats the copper mesh with a cationic polyelectrolyte solution and an anionic polyelectrolyte solution, and then repeatedly uses the cationic polyelectrolyte solution and the nano zeolite dispersion to impregnate the pre-treated copper mesh, and realizes the multi-layer assembly of nano zeolites through electrostatic adsorption, thereby obtaining a copper mesh with nano zeolites loaded on the surface, i.e., a copper mesh substrate.

[0012] Preferably, the cationic polyelectrolyte solution is prepared from polydimethyldiallylammonium chloride, ammonia water, sodium chloride and water.

[0013] By adopting the above technical solution, the present application selects polydimethyldiallylammonium chloride as the main component to prepare a cationic polyelectrolyte solution. After using this cationic polyelectrolyte solution in combination with an anionic polyelectrolyte solution, nano zeolite can be loaded on the surface of the copper mesh.

[0014] Preferably, the anionic polyelectrolyte solution is prepared from sodium polystyrene sulfonate, sodium chloride and water.

[0015] By adopting the above technical solution, the present application uses sodium polystyrene sulfonate as the main component to prepare an anionic polyelectrolyte solution. After the anionic polyelectrolyte solution is combined with a cationic polyelectrolyte solution, nano-zeolite can be loaded on the surface of the copper mesh.

[0016] Preferably, the nano zeolite dispersion is prepared according to the following method: (1) mixing an aluminum source, a template agent and water, and stirring to obtain an aluminum precursor liquid; mixing a silicon source, an inorganic base, a template agent and water, and stirring to obtain a silicon precursor liquid; (2) The aluminum precursor liquid is added into the silicon precursor liquid, and after stirring and heating under oil bath reflux, a nano-zeolite dispersion is obtained.

[0017] By adopting the above technical scheme, the present application first prepares silicon precursor liquid and aluminum precursor liquid separately, then mixes the silicon precursor liquid and the aluminum precursor liquid, and grows nano zeolite under the guidance of the template by oil bath reflux heating to obtain a nano zeolite dispersion.

[0018] Preferably, in step (4) of preparing the composite catalyst, silica sol is also added to the electrolyte.

[0019] By adopting the above technical solution, the silica sol added to the electrolyte in the present application can be combined with the modified copper mesh, and silicon dioxide is introduced on the surface of the modified copper mesh. Silicon dioxide can play a physical barrier role together with the nano-lanthanum oxide on the surface of the modified copper mesh, which helps to reduce the agglomeration of nano-silver.

[0020] Preferably, in step (4) of preparing the composite catalyst, nano-lanthanum oxide is also added to the cathode region of the electrolyte.

[0021] By adopting the above technical solution, the nano-lanthanum oxide added in the present application is initially mainly distributed in the cathode region and can be suspended in the electrolyte under the action of ultrasound. When nano-silver is generated in the cathode region, the nano-lanthanum oxide in the electrolyte can be deposited together with the nano-silver on the surface of the modified copper mesh as the cathode, and together with the nano-lanthanum oxide on the surface of the modified copper mesh, it plays a physical isolation role, which helps to reduce the agglomeration of nano-silver.

[0022] Preferably, in step (2) of the method, the oxygen-to-alcohol ratio of the reaction is 1-1.4.

[0023] By adopting the above technical solution, the present application selects the oxygen-to-alcohol ratio range of the reaction, and the preparation of glyoxal can be achieved within the above range and a good yield can be obtained.

[0024] Preferably, in step (2) of the method, the oxygen-to-alcohol ratio of the reaction is 1.1-1.5.

[0025] By adopting the above technical solution, the present application further optimizes the oxygen-to-alcohol ratio. When the oxygen-to-alcohol ratio is in the range of 1.1-1.3, the conversion rate of ethylene glycol is high and the side reaction products are relatively small, so glyoxal has a higher yield.

[0026] In summary, this application has the following beneficial effects: 1. The present invention uses the combined effects of copper mesh, zeolite and nano-lanthanum oxide to keep the nano-silver in the composite catalyst in a well-dispersed state and not easily agglomerate at high temperatures, thereby fully promoting the reaction of ethylene glycol conversion to glyoxal and helping to increase the yield of glyoxal.

[0027] 2. The present application prepares a zeolite-modified copper mesh containing nano-lanthanum oxide on the surface. The particle size of nano-silver is reduced by the physical isolation effect of nano-lanthanum oxide. In addition, the zeolite membrane and the copper mesh can be used as carriers of nano-silver together, thereby obtaining a composite catalyst in which nano-silver is evenly dispersed and not easy to agglomerate.

[0028] 3. In the present application, silica sol and nano-lanthanum oxide are added to the electrolyte. The nano-lanthanum oxide in the electrolyte, the silica sol and the nano-lanthanum oxide on the surface of the modified copper mesh can jointly play a role of physical isolation, which helps to reduce the agglomeration of nano-silver. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0030] Preparation example of composite catalyst The following is an explanation using Preparation Example 1.

[0031] Preparation Example 1 The cationic polyelectrolyte solution used in this preparation example was prepared as follows: A polydimethyldiallylammonium chloride aqueous solution with a solute content of 2 wt %, 0.1 M ammonia water, sodium chloride and distilled water were mixed in a weight ratio of 15:4:2.92:80 to obtain a cationic polyelectrolyte solution.

[0032] The anionic polyelectrolyte solution used in this preparation example was prepared as follows: Sodium polystyrene sulfonate, sodium chloride and distilled water were mixed in a weight ratio of 0.106:2.92:100 to obtain an anionic polyelectrolyte solution.

[0033] The nano-zeolite dispersion used in this preparation example was prepared according to the following method: (1) mixing an aluminum source, a template and water in a weight ratio of 0.15:3:4.49, and stirring to obtain an aluminum precursor liquid; mixing a silicon source, an inorganic base, a template and water in a weight ratio of 1.97:2.4:2:8, and stirring to obtain a silicon precursor liquid; in this step, the weight ratio of the silicon source to the aluminum source is 1.97:0.15, the aluminum source is aluminum foil, the silicon source is tetraethyl orthosilicate, the template is tetramethylammonium hydroxide aqueous solution (25wt%), and the inorganic base is 1M sodium hydroxide solution; (2) The aluminum precursor liquid was added to the silicon precursor liquid, stirred for 24 hours, and then refluxed in an oil bath at 100° C. for 3 days to obtain a nano-zeolite dispersion.

[0034] This preparation example provides a composite catalyst, which is prepared according to the following method: (1.1) washing a 300-mesh copper mesh, then immersing the copper mesh in a cationic polyelectrolyte solution, taking out the copper mesh after 30 minutes and washing it, then immersing the copper mesh in an anionic polyelectrolyte solution, taking out the copper mesh after 30 minutes and washing it, to obtain a pretreated copper mesh; (1.2) immersing the pretreated copper mesh in a cationic polyelectrolyte solution, taking out the copper mesh after 30 minutes and washing it, and then immersing the copper mesh in a nano-zeolite dispersion, taking out the copper mesh after 30 minutes and washing it; (1.3) Repeat step (1.2) 4 times to obtain a copper mesh substrate for later use; (2) Mixing an inorganic base, a silicon source, an aluminum source, nano-lanthanum oxide and distilled water in a weight ratio of 1.12:2.842:0.666:28 to obtain a growth solution for standby use; in this step, the inorganic base is sodium hydroxide, the silicon source is sodium silicate (calculated as sodium metasilicate), the aluminum source is aluminum sulfate, and the average particle size of the nano-lanthanum oxide is 10 nm; (3) immersing the copper mesh substrate in a zeolite growth solution and performing ultrasonic hydrothermal treatment at 80°C for 5 h to obtain a zeolite-modified copper mesh; (4) immersing the zeolite-modified copper mesh in a silver nitrate electrolyte with a silver nitrate concentration of 5 wt% as a cathode and a silver block as an anode at 55°C with a temperature of 16 Adm 2 The composite catalyst was obtained by electrolysis at a current density of 60 s and ultrasonic treatment at the same time, and then calcination at 500°C in an air atmosphere for 2 h.

[0035] Preparation Example 2 The difference between this preparation example and preparation example 1 is that in step (4) of preparing the composite catalyst, silica sol is further added to the electrolyte, and the silicon content in the silica sol is equivalent to 3% of the total weight of the electrolyte.

[0036] Preparation Example 3 The difference between this preparation example and preparation example 2 is that in step (4) of preparing the composite catalyst, nano-lanthanum oxide with an average particle size of 10 nm is added to the cathode region of the electrolyte, so that the concentration of nano-lanthanum oxide in the electrolyte is 5%. Example

[0037] Examples 1-5 The following description is given by taking Example 1 as an example.

[0038] Example 1 The present embodiment provides a method for synthesizing glyoxal by catalytic oxidation of a composite catalyst, comprising the following steps: (1) preheating and vaporizing ethylene glycol to obtain ethylene glycol vapor, mixing the ethylene glycol vapor, protective gas, air and circulating gas to obtain raw gas, and then preheating the raw gas for standby use; in this step, the protective gas is water vapor, the molar ratio of the protective gas to oxygen in the air is 5:1, and the oxygen-to-alcohol ratio (the molar ratio of oxygen to ethylene glycol vapor) of the raw gas is 1; (2) the raw gas is input into a catalytic reactor equipped with a composite catalyst, and the reaction is carried out under the conditions of 600° C. and 0.9 MPa. After the reaction is completed, the product is cooled to 200° C. with water, and then transported to an absorption tower for repeated absorption to obtain a crude glyoxal solution, and the crude glyoxal solution is distilled, purified and decolorized to obtain glyoxal; the composite catalyst used in this step is prepared according to the method of Preparation Example 1; (3) The tail gas is treated in the absorption tower and the scrubbing tower, and after the waste gas that meets the emission standards is discharged, the remaining tail gas is used as the circulating gas.

[0039] Example 2 The difference between this embodiment and embodiment 1 is that the composite catalyst used in step (2) is prepared according to the method of preparation example 2.

[0040] Example 3 The difference between this embodiment and embodiment 1 is that the composite catalyst used in step (2) is prepared according to the method of preparation example 3.

[0041] As shown in Table 1, the difference between Examples 3-7 is that the oxygen-to-alcohol ratio of the raw gas is different.

[0042] Table 1 Oxygen-to-alcohol ratio of raw gas sample Oxygen alcohol ratio Example 3 1 Example 4 1.1 Example 5 1.2 Example 6 1.3 Example 7 1.4 Comparative Example 1 The difference between this comparative example and Example 1 is that in the method for preparing the composite catalyst, the anionic polyelectrolyte solution is replaced with distilled water.

[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that in the method for preparing the composite catalyst, the cationic polyelectrolyte solution is replaced with distilled water.

[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that in the method for preparing the composite catalyst, sodium polystyrene sulfonate is removed from the anionic polyelectrolyte solution.

[0045] Comparative Example 4 The difference between this comparative example and Example 1 is that in the method for preparing the composite catalyst, the polydimethyldiallylammonium chloride in the cationic polyelectrolyte solution is removed.

[0046] Comparative Example 5 The difference between this comparative example and Example 1 is that in the method for preparing the composite catalyst, after washing the 300-mesh copper mesh, the step of loading nano zeolite on the surface of the copper mesh is omitted, and the copper mesh is directly used as a copper mesh substrate for hydrothermal treatment and subsequent operations.

[0047] Comparative Example Comparative Example 1 This comparative example provides a process for preparing glyoxal, comprising the following steps: After preheating and gasifying ethylene glycol, it is mixed with air and water vapor to obtain a mixed gas with an oxygen-to-alcohol ratio (molar ratio of oxygen to ethylene glycol) of 1. The mixed gas is input into a catalytic reactor equipped with 20-mesh catalyst particles, and the reaction is carried out under the conditions of a reaction temperature of 600°C and a reaction pressure of 0.9MPa. The reaction product is chilled to 230°C with water, and then sent to an absorption tower for absorption to obtain a finished product.

[0048] In this comparative example, the element composition of the catalyst is silver, phosphorus and silicon, and the weight proportions of the three elements are 99.2%, 0.3% and 0.5% respectively, and the remainder is inevitable impurities.

[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that the composite catalyst is prepared according to the same process as in Example 1 by removing the nano-lanthanum oxide in the growth solution.

[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that the composite catalyst is prepared according to the same process based on Preparation Example 1, except that a 300-mesh copper mesh is used as the cathode instead of the zeolite-modified copper mesh.

[0051] Performance testing methods The actual production of glyoxal in each embodiment and comparative example was detected, and the theoretical production of glyoxal was calculated according to the consumption of ethylene glycol. The yield of glyoxal was calculated according to the actual production and theoretical production of glyoxal. The results are shown in Table 2.

[0052] Table 2 Combining Example 1 and Comparative Example 1 with Table 2, it can be seen that the yield of glyoxal in Example 1 is significantly higher than that in Comparative Example 1. This is because the combined effect of the copper mesh, zeolite and nano-lanthanum oxide enables the nano-silver in the composite catalyst to maintain a good dispersion state and is not easy to agglomerate at high temperatures, thereby fully promoting the reaction of converting ethylene glycol into glyoxal and improving the yield of glyoxal.

[0053] Combining Example 1 and Comparative Examples 2-3 and Table 2, it can be seen that the glyoxal yield of Example 1 is significantly higher than that of Comparative Examples 2-3. This is because Comparative Examples 2-3 do not have the conditions for the copper mesh, zeolite and nano-lanthanum oxide to work together, and therefore nano-silver is still prone to agglomeration under high temperature conditions, which will affect the yield of glyoxal.

[0054] Combining Example 1 and Example 2 and Table 2, it can be seen that the glyoxal yield of Example 2 is higher than that of Example 1. This is because the silicon dioxide introduced by the silica sol on the surface of the modified copper mesh and the nano-lanthanum oxide on the surface of the modified copper mesh together play a physical barrier role, thereby reducing the agglomeration of nano-silver.

[0055] Combining Example 2 and Example 3 and Table 2, it can be seen that the glyoxal yield of Example 3 is higher than that of Example 2. This is because in the method for preparing the composite catalyst, the nano-lanthanum oxide in the electrolyte can play a physical isolation role together with the nano-lanthanum oxide on the surface of the modified copper mesh, thereby reducing the agglomeration of nano-silver.

[0056] In combination with Examples 3-7 and Table 2, it can be seen that although the preparation of glyoxal can be achieved within the range of an oxygen-to-alcohol ratio of 1-1.4, when the oxygen-to-alcohol ratio is within the range of 1.1-1.3, the conversion rate of ethylene glycol is higher. This is because the side reaction products within this range are relatively small, so glyoxal has a higher yield.

[0057] Combining Example 1, Comparative Examples 1-4 and Table 2, it can be seen that the glyoxal yields of Comparative Examples 1-4 are all low. This is because Comparative Examples 1-4 cannot achieve the synergistic coordination of anionic polyelectrolytes and cationic polyelectrolytes, making it difficult to fully load the nano zeolite on the copper mesh surface.

[0058] Combining Example 1, Comparative Example 5 and Table 2, it can be seen that the glyoxal yield of Example 1 is higher than that of Comparative Example 5. This is because the surface of the copper mesh of Comparative Example 5 is not loaded with zeolite, and it is difficult to achieve uniform dispersion of nanosilver using only the copper mesh as a carrier.

[0059] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A method for synthesizing glyoxal by catalytic oxidation using a composite catalyst, characterized in that: The following steps are involved: (1) Preheating and vaporizing ethylene glycol to obtain ethylene glycol vapor, mixing the ethylene glycol vapor, protective gas, air and circulating gas to obtain raw gas, and then preheating the raw gas for standby use; (2) introducing the raw gas into a catalytic reactor equipped with a composite catalyst, reacting under heating and pressurizing conditions, cooling the product with water after the reaction, and then transporting it to an absorption tower for repeated absorption to obtain a crude glyoxal solution, and distilling, purifying and decolorizing the crude glyoxal solution to obtain glyoxal; the composite catalyst is a copper mesh catalyst with zeolite, nano-silver and nano-lanthanum oxide loaded on the surface; (3) The tail gas is treated in the absorption tower and the scrubbing tower. After the exhaust gas that meets the emission standards is discharged, the remaining tail gas is used as circulating gas.

2. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 1, characterized in that, The composite catalyst is prepared according to the following method: (1) Loading nano zeolite on the surface of a copper mesh to obtain a copper mesh substrate for later use; (2) Mixing an inorganic base, a silicon source, an aluminum source, nano-lanthanum oxide and water to obtain a growth solution for later use; (3) immersing the copper mesh substrate into a zeolite growth solution for ultrasonic hydrothermal treatment to obtain a zeolite-modified copper mesh; (4) The zeolite-modified copper mesh is immersed in a silver nitrate electrolyte as a cathode, and silver is used as an anode for electrolysis, and ultrasonic treatment is performed. After the electrolysis is completed, the electrolysis product is calcined in air to obtain a composite catalyst.

3. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 2, characterized in that, In step (1) of preparing the composite catalyst, nano zeolite is loaded on the surface of the copper mesh according to the following method: (1) impregnating the copper mesh with a cationic polyelectrolyte solution and an anionic polyelectrolyte solution in sequence, then taking out the copper mesh and washing it to obtain a pretreated copper mesh; (2) impregnating the pretreated copper mesh with a cationic polyelectrolyte solution and a nano-zeolite dispersion solution in sequence, and then taking out the pretreated copper mesh and washing it; (3) Repeat step (2) multiple times to obtain a copper mesh substrate.

4. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 3, characterized in that, The cationic polyelectrolyte solution is prepared from polydimethyldiallylammonium chloride, ammonia water, sodium chloride and water.

5. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 3, characterized in that, The anionic polyelectrolyte solution is prepared from sodium polystyrene sulfonate, sodium chloride and water.

6. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 3, characterized in that, The nano zeolite dispersion is prepared according to the following method: (1) mixing an aluminum source, a template agent and water, and stirring to obtain an aluminum precursor solution; mixing a silicon source, an inorganic base, a template agent and water, and stirring to obtain a silicon precursor solution; (2) The aluminum precursor liquid is added into the silicon precursor liquid, and after stirring and oil bath reflux heating, a nano-zeolite dispersion is obtained.

7. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 2, characterized in that, In step (4) of preparing the composite catalyst, silica sol is also added to the electrolyte.

8. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 2, characterized in that, In step (4) of preparing the composite catalyst, nano-lanthanum oxide is also added to the cathode region of the electrolyte.

9. The synthetic method of composite catalyst catalytic oxidation of glyoxal according to claim 1, characterized in that: In step (2) of the method, the oxygen-alcohol ratio of the reaction is 1-1.

4.

10. The method for synthesizing glyoxal by catalytic oxidation of a composite catalyst according to claim 9, characterized in that: In step (2) of the method, the oxygen-to-alcohol ratio of the reaction is 1.1-1.5.